Henry: thomas & friends - Awdry, W. (Egmont London, 2008)
Henry is a green engine with a pompous personality. He often boasts about his strength and importance, but he is also quite sensitive and prone to sulking. Despite his flaws, Henry is a reliable engine who can be counted on when needed. He often gets into trouble due to his pride and impatience, but he learns valuable lessons along the way.